Pengaruh work-life conflict dan time pressure terhadap turnover intention dengan off-the-job embeddedness sebagai variabel moderasi pada Karyawan Generasi Z di Kota Semarang - Mertalizha, Dhella; Raharjo, Teguh Hardi (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the effects of work–life conflict and time pressure on turnover intention among Generation Z employees in Semarang, with off-the-job embeddedness as a moderating variable. Data were collected from 200 respondents through a questionnaire and analyzed using PLS-SEM with SmartPLS 4. The results indicate that both work–life conflict and time pressure significantly and positively influence turnover intention, with time pressure emerging as the strongest predictor. However, off-the-job embeddedness shows no significant direct or moderating effect. The model’s R-square value of 0.459 suggests that 45.9% of the variance in turnover intention is explained. Keywords: Work-Life Conflict; Time Pressure; Turnover Intention; Off-the-Job Embeddedness; Generation Z